Network-Coded Cooperative Systems With Generalized User-Relay Selection - Heidarpour, Ali Reza; Ardakani, Masoud; Tellambura, Chintha; Di Renzo, Marco; Uysal, Murat (IEEE transactions on wireless communications, 2020)
We consider a network-coded cooperative (NCC) system that consists of N \ge 2 sources, M\ge 1 decode-and-forward (DF) relays, and a single destination. The relays perform network coding (NC) on the received sources' symbols using maximum distance separable (MDS) codes. For this system, we propose the most generalized user-relay selection (GURS) scheme in the literature that selects any arbitrary subsets of K users and any arbitrary subsets of L relays subject to practical constraints such as load balancing conditions and scheduling policy. Our analytical results and design guidelines generalize and subsume all existing results as special cases. To this end, we derive a new closed-form outage probability (OP) expression, assuming non-identically and independently distributed (n.i.i.d.) Rayleigh fading channels. The asymptotic outage expression at high signal-to-noise ratio (SNR) regime is further derived, based on which, the achievable diversity order and coding gain are quantified. The theoretical derivations are also validated through Monte-Carlo simulation.